PENGARUH KOREAN WAVE TERHADAP SEKTOR PARIWISATA KOREA SELATAN TAHUN 2015-2018 - Khalifah, Muhammad Mifthakhul; Widhiyoga, Ganjar; Haqqi, Halifa (Solidaritas, 2020)
This study describes and analyzes the effect of the Korean Wave on the South Korea tourism sector in 2015-2018. Researchers use Commodification of Culture and Touism Concept as theories in conducting research. This study aims to find out how Korean Wave, a culture, can influence the tourism sector in South Korea. The method that researchers use in this study is a qualitative method with secondary data sources. The study was conducted through the collection of documents with descriptive elaboration. From research data on the influence of the Korean Wave on the South Korean tourism sector, researchers found that the increasing popularity of the Korean Wave can influence interest in South Korea, thereby affecting someone to visit South Korea directly. In other words Korean Wave can affect the tourism sector. Keywords: Korean Wave, Commodification of Culture, South Korean Tourism